2015
DOI: 10.5603/kp.a2015.0085
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent vascular response following delivery of sirolimus via fast releasing, biodegradable polymer stent matrix: an experimental study in the porcine coronary model of restenosis

Abstract: A b s t r a c tBackground: Fast releasing, rapamycin-eluting stents, although safe, showed inferior results with regard to inhibition of restenosis.Aim: Therefore, we report vascular effects of a novel, biodegradable polymer stent matrix with elevated sirolimus dose and fast release kinetics (ed-frSES, Alex, Balton) in the porcine coronary in-stent restenosis model. Methods:A total of 19 stents were implanted with 120% overstretch in the coronary arteries of seven domestic pigs: seven ed-frSES with 1.3 μg/mm 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Permanent polymers in drug-eluting stents used to overcome restenosis adversely affect the stented vascular restoration and prolong the inflammatory reaction process. Eventually, they contribute to late and very late thrombosis (9,18). When a biodegradable polymer is used, the drug is absorbed from the stent surface after elution, leaving only the neointima-and endothelium-coated metal stent without further irritating the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent polymers in drug-eluting stents used to overcome restenosis adversely affect the stented vascular restoration and prolong the inflammatory reaction process. Eventually, they contribute to late and very late thrombosis (9,18). When a biodegradable polymer is used, the drug is absorbed from the stent surface after elution, leaving only the neointima-and endothelium-coated metal stent without further irritating the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…This improves arterial vascular restoration and reduces the inflammatory reaction. It also reduces the need for long-term antiplatelet therapy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Investigator-driven initiatives are important to advance knowledge of new DES. A previous animal study reported the value of the Alex stent in inhibiting neointimal proliferation [8]. Another study, also from Poland, used optical coherence tomography to assess the mechanistic results of the Alex stent [9].…”
Section: Present Studymentioning
confidence: 98%
“…The biodegradable stent is thus considered a promising device for local treatment of ureter diseases. Moreover, the technology of rapamycin-eluting bioresorbable stent has become mature in treating coronary artery narrowing in the past decade [ 38 , 39 ]. In this study, a rapamycin-eluting bioresorbable stent is employed to test the hypothesis of improving ureteral stricture with local release of mTOR inhibitors (mTORi).…”
Section: Introductionmentioning
confidence: 99%